Microbiological assessment of 24- and 48-h changes and management of semiclosed circuits from ventilators in a neonatal intensive care unit. - Malecka-Griggs, B (1986)
The contamination of semiclosed disposable circuits of Healthdyne and Bourns ventilators was studied in a newborn intensive care unit over a 2-year period. A total of 379 fluid samples was obtained from inspiratory and expiratory tubing condensates and traps and from thermal humidifier columns fed with prefilled containers of sterile water. In addition, 100 tryptic soy agar plates were exposed to the exhalation mist of the circuits sampled. With 24-h changes of circuits a 2.5% contamination rate was observed (phase I). In an effort to contain costs, circuits were changed every 48 h (phase II); the concentration of potential pathogens increased to greater than 10(5) CFU/ml with this extension of changing time. Two long-term (15- and 9-month) infants were colonized and intermittently infected, one with Klebsiella pneumoniae and Staphylococcus aureus and the other with Pseudomonas aeruginosa. When the protocol was readjusted from 48- to 24-h circuit changes (phase II), the contamination rate decreased; for the two colonized infants (35 circuits, 123 samples) the contamination rate decreased from 19 to 6% (P less than 0.01; chi-square test), and for seven noncolonized infants (59 circuits, 217 samples) the contamination rate decreased from 5 to 0.5% P less than 0.001; (chi-square test). These data suggest that frequent changing of the circuits reduces colonization and cross-infection.